Armed conflict and gendered participation in agri-food systems: Survey evidence from 1.8 million individuals in 29 countries - Ronzani, Piero; Stojetz, Wolfgang; Azzarri, Carlo; Nico, Gianluigi; Mane, Erdgin; Brück, Tilman (International Food Policy Research Institute, 2023)
This paper provides empirical microlevel evidence on the gendered impacts of armed conflict on economic activity, combining sex-disaggregated employment survey data with temporally and spatially disaggregated conflict event data for 1.8 million individuals from 29 African countries. Specifically, we study several employment outcomes related to participation in agri-food systems. Agri-food systems are embedded in ecological, economic and social processes, drive nutrition outcomes and are critically important for the development of developing countries. On average, we find that local conflict exposure is only weakly related to labor force participation, but strongly reduces the total amount of hours worked and increases engagement in the agricultural sector. These net impacts exist for both men and women. However, the reduction in hours worked is significantly stronger among men, while the increase in agricultural activity is significantly stronger among women. In the longer term, conflict impacts on employment two years later are stronger when no more conflict ensues, challenging the widespread idea of one-off conflict shocks ‘fading away’ over time, and suggesting that labor markets adapt to and absorb lasting conflict situations. Different types of conflict events have qualitatively similar impacts, which are strongest for explosions, such as from air strikes or landmines. Overall, our findings underline that armed conflict entails structural economic, social and institutional change, which create complex, gendered impacts on economic activity and agri-food systems.